Spontaneous Escherichia coli bacterial meningitis mimicking heatstroke in an adult - Ishida, Kenichiro (Clin Case Rep, 2016)
Bacterial meningitis can be difficult to recognize: the meningeal triad symptoms are not always present and the alteration in mental status can mimic heatstroke. Escherichia coli meningitis is a serious disease whose early diagnosis, appropriate antibiotic treatment, and hemodynamic management are essential.